Stability analysis in chilli (Capsicum annuum L.) - S K Rao, B V Tembhurne, (Journal of Spices and Aromatic Crops, 2013)
Twenty cytoplasmic genetic male sterility (CGMS) based F1 hybrids, three promising genotypes and a check were evaluated in three different environments for stability analysis. The correlation and path coefficient analysis were studied in 75 genotypes for 18 and 12 different quantitative characters, respectively. Variance due to genotypes × environment interactions were significant for all the characters except number of fruits plant-1 and fresh fruit weight plant-1. Considering all the stability parameters, JCH-47, BCH-24 and BVC-37 exhibited wider stability for dry fruit yield plant-1, JCH-01 had stability for favourable environment and JCH-05, JCH-14, JCH-23, JCH-24, JCH-54 and RCH-23 showed below average stability. Highest performing F1 hybrid JCH-54 was identified as stable performer under unfavourable environment for dry fruit yield. The highest correlations were found with dry fruit weight plant-1 and fresh fruit weight plant-1 (r=1.00), number of fruits plant-1 (r=0.63), dry fruit weight fruit-1 (r=0.44), number of seeds fruit-1 (r=0.35), fresh fruit weight fruit-1 (r=0.32) and fruit length (r=0.28). Path analysis indicated that the number of fruits plant-1 and fresh fruit weight fruit-1 were the two factors that exerted the greatest influence both directly and indirectly upon the dry fruit yield. These two traits were the most important components that involved dry fruit yield plant-1.